Reinventing strategies for emerging markets: beyond the transnational model - London, Ted; Hart, Stuart L (Journal of International Business Studies, 2004)
With established markets becoming saturated, multinational corporations (MNCs) have turned increasingly to emerging markets (EMs) in the developing world. Such EM strategies have been targeted almost exclusively at the wealthy elite at the top of the economic pyramid. Recently, however, a number of MNCs have launched new initiatives that explore the untapped market potential at the base of the economic pyramid, the largest and fastest-growing segment of the world's population. Reaching the four billion people in these markets poses both tremendous opportunities and unique challenges to MNCs, as conventional wisdom about MNC global capabilities and subsidiary strategy in EMs may not be appropriate. How MNCs can successfully enter these low-income markets has not been effectively addressed in the literatures on global and EM strategies. An exploratory analysis, involving interviews with MNC managers, original case studies, and archival material, indicates that the transnational model of national responsiveness, global efficiency and worldwide learning may not be sufficient. Results suggest that the success of initiatives targeting low-income markets is enhanced by recognizing that Western-style patterns of economic development may not occur in these business environments. Business strategies that rely on leveraging the strengths of the existing market environment outperform those that focus on overcoming weaknesses. These strategies include developing relationships with non-traditional partners, co-inventing custom solutions, and building local capacity. Together, these successful strategies suggest the importance of MNCs developing a global capability in social embeddedness.